Upregulation of miRNA‐223‐3p ameliorates RIP3‐mediated necroptosis and inflammatory responses via targeting RIP3 after spinal cord injury. Issue 7 (28th February 2019) - Wang, Yang; Jiao, Jianhang; Ren, Pengfei; Wu, Minfei
Abstract: Spinal cord injury (SCI) has been a major burden on the society because of the high rate of disability. Receptor‐interacting protein 3 (RIP3)‐mediated necroptosis is a newly discovered pathway of programmed cell death and is involved in multiple pathologies of various human diseases. Micro RNAs (miRNAs) have been shown to be a potential target for therapeutic interventions after SCI. The aim of the present study is to explore the potential role of miR‐223‐3p and possible mechanism in SCI. We found that miR‐223‐3p was significantly downregulated in spinal neurons after H2 O 2 ‐induced damage, while RIP3‐mediated necroptosis was elevated. Accordingly, RIP3‐mediated necroptosis and the inflammatory factor secretion could be significantly inhibited by Nec‐1 treatment. In adittion, overexpression of miR‐223‐3p in spinal neurons protected against H 2 O 2 ‐induced necroptosis, and ablation of miR‐223‐3p exhibited the opposite effect. We found that miR‐223‐3p bound to the 3′‐untranslated region of RIP3 mRNA to negatively regulate the expression of RIP3. Moreover, the activated RIP3 reversed the inhibition of RIP3 and MLKL expression and the levels of TNF‐α, IL‐1β, and lactate dehydrogenase, which were induced by transfection with miR‐223‐3p in a H 2 O 2 ‐induced model. Finally, these results indicate that miR‐223‐3p negatively regulates the RIP3 necroptotic signaling cascades and inflammatory factor secretion, which significantly relieves injury of spinal neurons. The miR‐223‐3p/RIP3 pathway offers a novel therapeutic target for the protection of spinal neurons after SCI. Abstract : (1) miR‐223‐3p was significantly downregulated, while RIP3‐MLKL–mediated necroptosis was highly elevated in spinal neurons after spinal cord injury (SCI). (2) Overexpression of miR‐223‐3p in spinal neurons protected against H2 O 2 ‐induced necroptosis and ablation of miR‐223‐3p exhibited the opposite effect. (3) miR‐223‐3p was binding to the 3‐untranslated region of receptor‐interacting protein 3 (RIP3) messenger RNA to negatively regulate the expression of RIP3. miR‐223‐3p negatively regulated the RIP3‐MLKL necroptotic signaling cascades and inflammatory factor secretion, which significantly relieved SCI. (4) The activated RIP3 reversed the inhibition of RIP3 and mixed‐lineage kinase domain‐like (MLKL) expression and the levels of TNF‐α, IL‐1β, and lactate dehydrogenase, which was induced by transfection with miR‐223‐3p in a H2 O 2 ‐induced model.